Assessment of bidirectional relationships between hypothyroidism and endometrial cancer: a two-sample Mendelian randomization study - Wang, Bolin; Luo, Yuxi; Liu, Tianxin; Xu, Shengnan; Pei, Jinli; Liu, Jie; Yu, Jinming (Frontiers in Endocrinology, 2024)
Objective: Hypothyroidism, characterized by reduced thyroid hormone levels, and endometrial cancer, a prevalent gynecological malignancy, have been suggested to have a potential association in previous observational studies. However, the causal relationship between them remains uncertain. This study aimed to investigate the causal relationship between hypothyroidism and endometrial cancer using a bilateral Mendelian randomization approach.Methods: A bidirectional two-sample Mendelian randomization study was conducted using summary statistics from genome-wide association studies to identify genetic variants associated with hypothyroidism and endometrial cancer. The inverse variance weighting method was used as the main analysis, and sensitivity analyses were conducted to validate the MR results.The results of our analysis did not support a causal effect of hypothyroidism (OR: 0.93, p=0.08) or autoimmune hypothyroidism (OR: 0.98, p=0.39) on endometrial cancer risk.In the reverse MR analysis, we did not find a significant causal effect of endometrial cancer on hypothyroidism (OR: 0.96, p=0.75) or autoimmune hypothyroidism (OR: 0.92, p=0.50).Based on subgroup analysis by pathological subtypes of endometrial cancer, the above findings were further substantiated((all p-value ＞0.001).Our Mendelian randomization analysis suggests a lack of causal association between hypothyroidism and endometrial cancer. To gain a deeper understanding of this association, it is essential to conduct large-scale randomized controlled trials in the future to validate our findings.